Spatial behaviour of reintroduced male buffalo and their response to predators - Nkanyiso, Cele (My University, 2019)
Understanding spatial behavior of reintroduced animals is critical for better informed management decisions. Rapid growth of human population has caused human and wildlife species conflict over the years. Exploitation of resources for human consumption destroys and fragments natural habitats, decreases species diversity and distribution and fast-tracks the rate of extinction. Large herbivores are often translocating and reintroduced as a process of re-establishment. Reintroduction success depends on numerous factors, which include; the handling and capturing procedure, availability of food, habitat quality, the interaction of the species at the release location, and most importantly, post release monitoring. The adaptive local convex hull (a-LoCoH) was applied to study home range establishment and utilization of the two-male buffalos in the Dinokeng Game Reserve, South Africa from 2012 to 2014. Movement patterns were similar between the two-male buffalo over the same time period, with home range establishment in the core and 95% reaching 4.11 km2 and 19.36 km2 for male buffalo 427 and 6.20 km2 and 41.79 km2 for male buffalo 455, respectively. Stabilization of movement pattern became apparent after 180 days of reintroduction suggesting change in movement pattern/behavior from large scale exploration to small scale exploration. Furthermore, the buffalo’s showed avoidance and seasonal avoidance of built-up and lion probability of occurrence areas, respectively. The study shows the importance of biotic and abiotic factors that influence buffalo movement pattern and resource selection.